2017
DOI: 10.3390/genes8120392
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Relationship between Obesity and Various Diseases from a Network Perspective

Abstract: The number of obesity cases is rapidly increasing in developed and developing countries, thereby causing significant health problems worldwide. The pathologic factors of obesity at the molecular level are not fully characterized, although the imbalance between energy intake and consumption is widely recognized as the main reason for fat accumulation. Previous studies reported that obesity can be caused by the dysfunction of genes associated with other diseases, such as myocardial infarction, hence providing ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…Therefore, we mapped these three gene lists onto the comprehensive functional association network of STRING 34 , a widely used network for bioinformatics studies [35][36][37][38] . Only the high confidence interactions of STRING were included, in other words, the confidence score of the interaction must be greater than 0.900.…”
Section: The Network Expansion Of Nac Mpfc and Pag Neuropathic Pain mentioning
confidence: 99%
“…Therefore, we mapped these three gene lists onto the comprehensive functional association network of STRING 34 , a widely used network for bioinformatics studies [35][36][37][38] . Only the high confidence interactions of STRING were included, in other words, the confidence score of the interaction must be greater than 0.900.…”
Section: The Network Expansion Of Nac Mpfc and Pag Neuropathic Pain mentioning
confidence: 99%
“…Furthermore, SB's potential impact on thyroid hormone synthesis, energy metabolism, and body temperature regulation is notable. The observed gene enrichment related to insulin secretion in visceral fat tissues implies that SB might indirectly heighten the risk of metabolic diseases like diabetes, a significance also emphasized in the study by Chen et al [56]. This comprehensive analysis enhances our understanding of the complex genetic underpinnings, biological mechanisms, and their association with obesity.…”
Section: Plos Onementioning
confidence: 55%
“…Enrichment analysis showed that these modules are related to diseases that involve cell adhesion, to the innate immune response, and to cardiovascular and hypertensive diseases, providing biological insights into weight gain during pregnancy. PPI networks have been studied in chronic diseases such as obesity ( Chen et al, 2017 ; Chen et al ., 2021 ) and in gestational diabetes mellitus ( Zhu et al, 2020 ) but have not yet been described in maternal EGWG.…”
Section: Discussionmentioning
confidence: 99%